NAVIGATING IDENTITY AND CULTURAL CONSTRUCTS: A COMPARATIVE ANALYSIS OF SPIRITED AWAY AND A TERRIBLE MATRIARCHY - Tungoe, Chumdemo (International Journal of Research -GRANTHAALAYAH, 2024)
The objective of this study is to analyze, explore and compare the two completely different stories of Spirited Away by Hayao Miyazaki and A Terrible Matriarchy by Easterine Kire. The cultural, thematic, narrative and the world view of the child of both works will provide the thematic framework of this study. Miyzaki’s Spirited Away occurs in a completely realm of its own, the world supernatural and spirits while the events of Kire’s A Terrible Matriarchy takes place in a regular and traditional setting of a Naga society. Even though both stories take place in a completely different world and realm, they have uncanny resemblance in terms of literary perspective. The study seeks to establish a bridge connecting these two works by establishing a fresh perspective by understanding both cultures, their outlook towards life and its presentation in their works.